Soft matter the stuff that dreams are made of - Piazza, Roberto (Dordrecht, Netherlands Copernicus Dordrecht, 2011)
Soft matter may, as Roberto Piazza puts it, be the stuff of dreams, but it is also the stuff of life. That is what makes this book so engaging ? because it shows the ingenuity that both nature and humankind have invested in the bendy, stretchy, fragile, tough and adaptable substances we find all around us. There is plenty of hard science in this soft matter, and Piazza offers an urbane and eloquent tour through it.? Philip Ball, multi-award winning science writer. This book takes you for a leisurely walk through the ?middle earth? that scientists call soft matter much smaller than what we observe with the naked eye, but not as remote as the esoteric realm of molecules, atoms and fundamental particles. From toys to trainers, our civilization would be very different if we did not have plastic. From milk to paint, what would we do without colloids? We ourselves fall into the category of soft matter, made as we are of a molecular origami of proteins, DNA and other biological compounds. This fascinating exploration reveals what these materials have in common and which aspects of their behavior make them useful in our everyday life. Understanding more about their physical properties will make you marvel at the ?soft? things that surround us. With a Foreword by Professor Henk Lekkerkerker, Utrecht University, the Netherlands Roberto Piazza trained as a physicist at the school of Vittorio Degiorgio, and is now a professor of Condensed Matter Physics at the Politecnico di Milano, Italy, Associate Editor of the European Physical Journal E and coordinator of the European Space Agency's Topical Team for Applications of colloids in microgravity of the European Space Agency. He has made important contributions to research on nanoparticle suspensions, polymer and surfactant solutions and  biological macromolecules. He is not only a gifted physicists, but equally well versed in history and literature
Foreword -- Preface to the English edition -- 1 Overture: a special day -- 2 A life in suspense -- 3 Freedom in chains -- 4 Double-faced Janus Molecules -- 5 Nanoarchitecture -- 6 Dreamtime -- Weird words: soft matter from A to Z -- Index of common things (or almost so).
Electronic reproduction.
Keywords: Chemistry, Physical and theoretical; Soft condensed matter